Design of Compact and Wideband Suppression Low Pass Elliptic Filter by n-Segment Step Impedance Transmission Line - Hayati, M.; Amiri, M.; Sedighy, S. H. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, the invasive weed optimization technique for compacting a microstrip elliptic low pass filter is proposed and validated. At the first step, the invasive weed optimization (IWO) technique is used to replace the shunt resonators transmission lines of the conventional filter with arbitrary n-segments Step Impedance Transmission Lines (SITLs) for compacting it. To validate the proposed method, the shunt resonator transmission lines of a seventh-order elliptic lowpass filter are replaced with proper SITLs which cause more than 30% compactness in this step. Then the IWO technique is applied on the general filter configuration to design a wideband harmonic suppression and compact elliptic low pass filter. This method extends the stop band bandwidth more than 8.5 f0 and also increases the compactness to 47%. The measurement results of the final optimized fabricated filter are in good agreement with the simulation ones.